TEACHING STRATEGIES FOR DEVELOPING THE STUDENTS' LISTENING COMPREHENSION SKILLS - Erisa Kurniati (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This article is talking about teaching listening, which always said as the boring class and quite. Here the students always feel difficult before they try. Listening class always identical with listen and mention or fill in the blank or answer the question so must keep silent. The same strategies always be done and finally students spend their time with sleeping in the class. Actually, there are some stratesies for teaching listening cornprehension to develop students' skills; they are Cognitive and Meta cognitire straregies. How we combine it both and use it well so students can develop their listening skills. Here we can make the class more interactive. In listening subject, there are two processes they are bottom up process and top down process. It is needed to get the information from the audio or video that they hear. The students not only hear, fill the blanks, and answer the questions, but they also discuss or debate it in conversation each other or in the group, and teacher also can make the role-play here so make the class more fun and interactive. Everyone will participate in listening class so it is mean develop their skills in hearing, grammar, pronunciation, vocabulary, and speaking. Teacher assess the listening with their application. how good they get the information from the audio or video and can discuss (playing games. debates, or Discussion) it with the other students in class.